FINANCIAL DEVELOPMENT AND ROMANIAN SMES - DANIELA-RODICA SILIVESTRU (POPESCU) (Challenges of the Knowledge Society)
Research has shown that financial development accelerates economic growth but little has been discussed about the disproportionate effect a country’s financial development has on the growth of its small firms. With this in mind we propose a panel data analysis of the Romanian SMEs over the period 2002-2008. The results show that financial development exerts a positive effect on small firms relative to large ones. The analysis is based on data regarding: (a) the relative size of Romanian small and medium size enterprises (SMEs) in sectors like: industry, trade and services (calculated as the share of value added by different size class SMEs in total country’s value added); (b) each sector’s employment share and (c) Romania’s level of financial development.